Genome-wide characterization of the CPA gene family in potato and a preliminary functional analysis of its role in NaCl tolerance - Liu, J.; Li, D.; Wang, J.; Wang, Q.; Guo, X.; Fu, Q.; Kear, P.; Zhu, G.; Yang, X. (Springer, 2024)
Background The cation/proton antiporter (CPA) superfamily plays a crucial role in regulating ion homeostasis and pH in plant cells, contributing to stress resistance. However, in potato (Solanum tuberosum L.), systematic identification and analysis of CPA genes are lacking.